The ethnic canon : histories, institutions, and interventions - Palumbo-Liu, David (University of Minnesota Press, 1995)
Argues that texts are added to the canon only after an operation that attempts to resolve and neutralize historical and political contradictions and differences. The Ethnic Canon offers a wide variety of critical viewpoints and is unique in its pointed critique of the academy regarding specific authors and texts that have and have not been included in the canon.